-4x+9=-39

Simple and best practice solution for -4x+9=-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+9=-39 equation:


Simplifying
-4x + 9 = -39

Reorder the terms:
9 + -4x = -39

Solving
9 + -4x = -39

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -4x = -39 + -9

Combine like terms: 9 + -9 = 0
0 + -4x = -39 + -9
-4x = -39 + -9

Combine like terms: -39 + -9 = -48
-4x = -48

Divide each side by '-4'.
x = 12

Simplifying
x = 12

See similar equations:

| b/1+6=2 | | -x+6=-21+8x | | u=3(5-u)+1 | | 4+6x=-62 | | 3(3x-4)=2x-8 | | 4t+3(2-t)=13 | | 2+7x=-5 | | -6(3x+6)+2= | | 3x+4=-5+2x | | -7x-8=-71 | | -7-2x=-9 | | (2t^2-t-6)(2t^2+2t-1)= | | 7(2y-3)=-16 | | -5+4x=35 | | 40+35=b | | 5n+8n= | | 64=-16x^2+80x | | 3-p-4+p= | | 3(4x+12)=48 | | 45+35c=b | | 1-5a+a-8= | | 1607-1531= | | 118=-16x^2+80x | | 5q-6=2(q+3) | | v+4v= | | -1(x-4)+2=6(x+3) | | 4x+11x=-2 | | 6+3x=-15-4x | | m-4-6m= | | 3(3k+6)-8= | | 2x-9+5+6x= | | 10y=3x |

Equations solver categories